2015
DOI: 10.1016/j.biopsych.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Novel Positive Allosteric Modulator of Metabotropic Glutamate Receptor 2 AZD8529 on Incubation of Methamphetamine Craving After Prolonged Voluntary Abstinence in a Rat Model

Abstract: Background Cue-induced methamphetamine craving increases after prolonged forced (experimenter-imposed) abstinence from the drug (incubation of methamphetamine craving). Here, we determined whether this incubation phenomenon would occur under conditions that promote voluntary (self-imposed) abstinence. We also determined the effect of the novel mGluR2 positive allosteric modulator, AZD8529, on incubation of methamphetamine craving after forced or voluntary abstinence. Methods We trained rats to self-administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
147
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 88 publications
(123 reference statements)
10
147
2
Order By: Relevance
“…We found that under both training conditions, methamphetamine seeking in the extinction tests was higher after 21 abstinence days than after 1 day, demonstrating incubation of drug craving after voluntary abstinence. We also found that 'incubated' drug seeking on voluntary abstinence day 21 was similar in magnitude to the incubated drug seeking observed on forced abstinence day 21 (Caprioli et al, 2015a).…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…We found that under both training conditions, methamphetamine seeking in the extinction tests was higher after 21 abstinence days than after 1 day, demonstrating incubation of drug craving after voluntary abstinence. We also found that 'incubated' drug seeking on voluntary abstinence day 21 was similar in magnitude to the incubated drug seeking observed on forced abstinence day 21 (Caprioli et al, 2015a).…”
Section: Introductionsupporting
confidence: 54%
“…Between tests, the rats underwent voluntary abstinence for 19 days (achieved via a mutually exclusive discrete choice procedure between methamphetamine and the palatable food in which, on any given trial, the rats can earn the food or drug reward but not both; 20 trials/day). Under our voluntary abstinence procedure, most rats achieve complete methamphetamine abstinence during most of the choice sessions (ie, zero choices of methamphetamine infusions), whereas some rats continue to occasionally self-administer a small number of drug infusions during these sessions (Caprioli et al, 2015a;Caprioli et al, 2016;Caprioli et al, 2015b) (see Figure 2). We found that under both training conditions, methamphetamine seeking in the extinction tests was higher after 21 abstinence days than after 1 day, demonstrating incubation of drug craving after voluntary abstinence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic administration of this compound decreases cued nicotine intake and cue-and nicotineinduced seeking (Justinova et al, 2015) as well as cueinduced methamphetamine seeking (Caprioli et al, 2015). Interestingly, AZD8529 was effective at inhibiting cued nicotine seeking at doses that did not affect food seeking, indicating that the selective activation of mGluR2 may prove a more effective treatment of relapse given the lack of a negative effect on natural rewards.…”
Section: Group II Metabotropic Glutamate Receptors (Metabotropic Gmentioning
confidence: 99%